Capacity precommitment, communication, and collusive pricing: Theoretical benchmark and experimental evidence - Werner Güth; Manfred Stadler; Alexandra Zaby (University of Tübingen, Faculty of Economics and Social Sciences, 2018)
In a capacity-then-price-setting game we experimentally identify capacity precommitment, the possibility to communicate before price choices, and prior competition experience as crucial factors for collusive pricing. The theoretical analysis determines the capacity thresholds above which firms have an incentive to coordinate on higher prices. The experimental data reveals that such intra-play communication after capacity but before price choices has a collusive effect only for capacity levels exceeding these thresholds. Subjects with high capacities generally choose higher prices when they have the possibility to communicate. Asymmetry in capacity choices decreases the truthfulness of price messages as well as the probability to coordinate on the same price.
urn:nbn:de:bsz:21-dspace-850718
Keywords: C72; C91; L1; 330; capacity-then-price competition; excessive capacities; cheap talk; intra-play communication; collusion; experimental economics